IMPLEMENTASI BUSINESS INTELLIGENCE UNTUK MENENTUKAN TINGKAT KEPOPULERAN JURUSAN PADA UNIVERSITAS - Ricky Akbar; Ria Oktaviani; Shabrina Tamimi; Syifa Shavira; Tri Winda Rahmadani (Jurnal Ilmiah Informatika, 2017)
In this globalization era that we face nowadays, information technology is the most important thing to be learnt or just to be known. Because in this all-sophisticated era, almost all the live's aspects are related with information and technology. It's not exception to determine the level of major popularized in on of University. In it's implementation, for sure it's difficult to determine which major is being the most popular, because there are so many data, so the process of decision making run slowly if it is done with standard query on database. Here is the used of Business Intelligence is really needed. By implemented Business Intelligence, the big data can be processed without any difficulties. On this research, application that we use is TABLEAU. TABLEAU is chosen because of its ease and its velocity on processing data. So that, it's hoped can ease in decision making for determining the most popular major at Andalas University.